Analisis Tingkat Efisiensi Aktivitas Produksi Menggunakan Metode Data Envelopment Analysis (DEA) Model BCC 2-Stage Produksi Tas - Sofiani, Gizella; Nurwidiana, Nurwidiana (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Efficiency improvements are always carried out on an ongoing basis to be able to meet market needs.  A garment manufacturing company making travel bags has been experiencing problems in meeting production targets. Efficiency measurements need to be carried out with aim of knowing the level of efficiency of the production process, and factors that influence inefficiency, and there is a need for proposed improvements to optimize the efficiency of the production process. The efficiency value is measured using the Data Envelopment Analysis (DEA) method. The efficiency of the production process was measured by 12 DMUs with 4 input variables and 3 output variables. The variables used include the number of workers, working hours, wages, production targets, production results, output hours, and product prices. Analysis of processing efficiency using the BCC model DEA method with the help of the Win4Deap2 program shows that 6 DMUs are declared efficient and 6 other DMUs are inefficient. Inefficient DMUs are DMU 2 97.4%, DMU 3 91.2%, DMU 6 99.8%, DMU 8 96.2%, DMU 9 97.1%, DMU 11 87.3% . There needs to be improvements to the 6 inefficient DMUs by referring to the efficient DMUs. Keywords: Data Envelopment Analysis, Efficiency, Production Process